Isolation and Characterization of Biosurfactant-Producing Bacteria from Amapaense Amazon Soils. (17th August 2021) - Oliveira, Elisa Maria de; Sales, Victor Hugo Gomes; Andrade, Marcelo Silva; Zilli, Jerri Édson; Borges, Wardsson Lustrino; Souza, Tiago Marcolino de
Abstract : The objective of this research was to perform screening of biosurfactant-producing bacteria from Amapaense Amazon soils. Floodplain- and upland-forest soils of three municipalities of the Amapá state were isolated and identified. The isolates were cultured in nutrient broth with olive oil, and their extracts were evaluated according to drop collapse, oil dispersion, emulsification, and surface tension tests. From three hundred and eighteen isolates, the 43 bacteria were selected and identified by 16S rDNA gene sequencing, indicating the presence of three different genera, Serratia, Paenibacillus, and Citrobacter . The extracellular biosurfactant production pointed out the 15 most efficient bacteria that presented high emulsification capacity ( E 24 > 48%) and stability (less than 10% of drop after 72 h) and great potential to reduce the surface tension (varying from 49.40 to 34.50 mN·m −1 ). Cluster analysis classified genetically related isolates in different groups, which can be connected to differences in the amount or the sort of biosurfactants. Isolates from Serratia genus presented better emulsification capacity and produced a more significant surface tension drop, indicating a promising potential for biotechnological applications.